2020
DOI: 10.1016/j.ultramic.2019.112890
|View full text |Cite
|
Sign up to set email alerts
|

Patterned probes for high precision 4D-STEM bragg measurements

Abstract: Nanoscale strain mapping by four-dimensional scanning transmission electron microscopy (4D-STEM) relies on determining the precise locations of Bragg-scattered electrons in a sequence of diffraction patterns, a task which is complicated by dynamical scattering, inelastic scattering, and shot noise. These features hinder accurate automated computational detection and position measurement of the diffracted disks, limiting the precision of measurements of local deformation. Here, we investigate the use of pattern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 46 publications
2
89
0
Order By: Relevance
“…Using test data obtained in the SPED mode of acquisition (Vincent & Midgley, 1994) of a custom system (MacLaren et al, 2020), we demonstrate that a lattice parameter fractional precision of 6 ×10 −4 is possible using a probe with a spatial resolution of 1.1 nm. This precision value is approximately 2–3× larger than the best ones reported in the literature using standard probes in a SPED mode (Rouvière et al, 2013) and patterned probes in standard STEM mode (Guzzinati et al, 2019; Zeltmann et al, 2020).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Using test data obtained in the SPED mode of acquisition (Vincent & Midgley, 1994) of a custom system (MacLaren et al, 2020), we demonstrate that a lattice parameter fractional precision of 6 ×10 −4 is possible using a probe with a spatial resolution of 1.1 nm. This precision value is approximately 2–3× larger than the best ones reported in the literature using standard probes in a SPED mode (Rouvière et al, 2013) and patterned probes in standard STEM mode (Guzzinati et al, 2019; Zeltmann et al, 2020).…”
Section: Introductionmentioning
confidence: 61%
“…At the small level of material distortion found here, the fractional precision of the lattice parameters is the same as that of the associated strain parameters. Very recent reports of strain measurements using patterned probes in the literature (Guzzinati et al, 2019; Zeltmann et al, 2020) approach the best values reported from standard Airy probes in SPED acquisitions (Rouvière et al, 2013), but with potential benefits of improved dose efficiency. The fractional precision of 6 × 10 −4 obtained here with a DED is approximately 3× higher than the value from the latter (of ≤ 2 × 10 −4 ) with a similar spatial resolution, but using exposures 100× smaller and a detector with 64× fewer pixels (256 × 256 DED versus a 2k × 2k CCD).…”
Section: Lattice Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…In this talk we introduce an alternative method of simultaneously recording diffraction patterns with multiple beam tilts: multi-beam electron diffraction (MBED). We produce these beams with a modified condenser system in a ThermoFisher Titan instrument similarly to [5], with a schematic and some experimental results shown in Figure 1. In this experiment, eight simultaneous diffraction patterns were recorded from a single crystal of gold, covering an angular range of +/-3 degrees.…”
mentioning
confidence: 99%